Pengembangan Media Pembelajaran Berbasis Android QuickAppNinja (Guess Image & Find Words) Untuk Meningkatkan Literasi Digital Guru Sekolah Dasar - Syaiful Bakhri; Nabeela Himmatus Tsuroya; Yanwar Pratama (Jurnal Penelitian Pendidikan IPA, 2023)
In the era of the industrial revolution 4.0, all forms of technological progress were massively implemented in various aspects of life, including education. Teachers must have skills in media, information, and internet networks, constructed as Digital Literacy skills. This study aims to develop learning media on the material at the elementary school level based on Android application techniques that teachers can use in learning activities. The research covers the stages of developing Android-based learning media using QuickAppNinja (student learning tools include searching for words and guessing pictures), then measuring the teacher's response to the developed application, and how digital literacy skills change in teachers after using the developed learning media. The research method adopts a design and development (D&D) model, including setting objectives, aligned assessments, making flowcharts and storyboards, selecting or creating media, creating interfaces, and integration. The instrument of research was used in the form of a multiple choice test that measures the respondent's digital literacy. Test results from 35 teachers, with an average score of 7.27 out of 10, mean the teacher is sufficiently mastering digital literacy skills.